2005
DOI: 10.1128/aem.71.9.5383-5390.2005
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Relatedness of Vancomycin-Resistant Enterococci in Animals, Humans, and the Environment in Different European Regions

Abstract: Vancomycin-resistant enterococcci (VRE) in Europe are thought to have emerged partly due to the use of the glycopeptide avoparcin in animal husbandry. We compared the occurrence of VRE in geographical regions of Europe in which until 1997 large amounts of avoparcin were used (Spain, United Kingdom, and Denmark) with the occurrence of VRE in Sweden, where avoparcin was banned in 1986. We also studied the relatedness between VRE strains from different regions and habitats. In total, 2,580 samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 49 publications
(36 reference statements)
4
74
1
2
Order By: Relevance
“…The study by Gambarotto et al showed that the prevalence of VRE in hematology patients was about 37% (25). Kuhn et al showed that the prevalence of VRE isolated from animals, humans and the environment in different European regions was in the range of 8% -11% (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Gambarotto et al showed that the prevalence of VRE in hematology patients was about 37% (25). Kuhn et al showed that the prevalence of VRE isolated from animals, humans and the environment in different European regions was in the range of 8% -11% (16).…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus spp. may carry various genes that directly or indirectly contribute to virulence (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In hospital settings, multidrug-resistant bacteria are being isolated at an increasing rate and are having a significant impact on clinical practice and overall treatment cost (7,15). Furthermore, in the community, a pool of antibiotic-resistant bacteria exists that either originates from hospital reservoirs or is a consequence of the use of antimicrobial substances in animals (14).…”
mentioning
confidence: 99%
“…In our study, 25% of clinical isolate and 66.7% of stool isolate were resistant to vancomycin, these results agreed with those of other results (Al Kafaji, 2005), but in disagreement with that of (Alsaadi, 2007) which showed that all isolates of E. faecalis were sensitive to vancomycin but in the study of (Kandela, 2006) the resistance was higher the current study. Kühn et al, (2005) studied the occurrence of VRE in 2 580 samples collected in different geographical regions in Europe, high proportions of VRE-positive urban sewage samples were found in Sweden, Spain, and the United Kingdom (52 to 90%), apparently reflecting a human source rather than an animal source; despite the fact that the consumption of antibiotics in hospitals in Sweden (population, 9 million) is among the lowest in Europe. Thus, it is possible that antibiotic-resistant enterococci present in the human population are enriched in hospitals, released from there into municipal sewers to become established, and then further released via sewage treatment plants into recipient water and transferred back into humans.…”
Section: Discussionmentioning
confidence: 99%